Chemical Composition of Essential Oils of Aromatic and Medicinal Herbs Cultivated in Greece—Benefits and Drawbacks - Ioannis N. Pasias; Dimitris D. Ntakoulas; Kalomoira Raptopoulou; Chrysavgi Gardeli; Charalampos Proestos (Foods, 2021)
The current study investigated and determined the major compounds of six essential oils derived from different plant species cultivated in Greece (Lavandula angustifolia, Origanum vulgare, Pistacia lentiscus var. chia, Citrus reticulata, Citrus limon and Crithmum maritimum). The results proved that all these essential oils have a high potential for use as food preservatives, since among the compounds determined were sabinene, b-myrcene, a-pinene, carvacrol and limonene, all of which were responsible for the strong antimicrobial activity against Staphylococcus aureus. However, the amounts of some compounds, such as linalool and citral, were at high levels, and this can be a danger for some sensitive population groups due to allergic reactions. The essential oil compounds which were identified using GC-MS and quantified through GC-FID represented more than 95% of the total essential oils of the investigated plant species. Finally, all essential oils provided high phenolic content.